2019
DOI: 10.21009/1.05212
|View full text |Cite
|
Sign up to set email alerts
|

A Problem Based Learning: Practicing Students' Critical Thinking Skills with Cognitive Style Dependent Fields and Independent Fields

Abstract: The critical thinking skills require to be possessed by students to decide to gain new knowledge. The perception differences by each student influence students' thinking skills have, so to practice these skills is a needed learning approach to the student truly. One of them is problem-based learning. The purpose of this study is to train students' critical skills who have the cognitive method of Field Independent (FI) and Field Dependent (FD). This type of research is experimental research. The sampling techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…The results of previous studies [35] showed that learners with FI cognitive styles tended to be stronger in using their critical thinking than FD. Likewise, the results of a study by Listiagfiroh & Ellianawati [36], their findings were that FI learners were better at critical thinking compared to FD learners. The FD learners need guidance in the process of solving problems and the use of critical thinking.…”
Section: Resultsmentioning
confidence: 88%
“…The results of previous studies [35] showed that learners with FI cognitive styles tended to be stronger in using their critical thinking than FD. Likewise, the results of a study by Listiagfiroh & Ellianawati [36], their findings were that FI learners were better at critical thinking compared to FD learners. The FD learners need guidance in the process of solving problems and the use of critical thinking.…”
Section: Resultsmentioning
confidence: 88%
“…Partisipasi guru aktif terletak pada pelayanan selama berlangsungnya proses pembelajaran. Mempertimbangkan kondisi dan keberagaman kebutuhan belajar siswa perlu adanya pemilihan dan penggunaan model pembelajaran yang efektif dan efisien (Listiagfiroh & Ellianawati, 2019) Tahap-tahap perencanaan sebelum mengunakan model VAK dengan teknik WBT sebagai model pembelajaran di MI Nurul Huda disampaikan oleh kepala sekolah tentang pelaksanaan kelanjutan pelaksanaan pelatihan Training of Trainer (ToT) untuk guru serta penerapan RPP dalam menggunakan model pembelajaran VAK dengan teknik WBT di MI Nurul Huda Kecamatan Bergas Kabupaten Semarang. Gaya belajar merupakan bentuk tanggung jawab yang menjadikan siswa harus mengadaptasi terhadap strategi tertentu selama proses kegiatan belajar karena adanya tuntutan pelajaran khusus di kelas maupun dari mata pelajaran tertentu pada setiap sekolah.…”
Section: Hasil Dan Pembahasan Perencanaan Model Vak Dengan Teknik Wbt...unclassified
“…Penelitian menurut (Ruskandi & Ferdian, 2016) menunjukkan penerapan pendekatan CTL dalam pembelajaran IPS SD tidak hanya berpengaruh terhadap keterampilan berpikir kritis saja tetapi berpengaruh juga terhadap hasil belajar siswa. Penelitian menurut (Listiagfiroh & Ellianawati, 2019) menunjukkan keterampilan berpikir kritis ditinjau dari gaya kognitif field independent dan field dependent dapat disimpulkan bahwa rata-rata skor gaya kognitif siswa adalah 10,35. Hal ini membuktikan bahwa sebagian besar siswa SMK nuruk hadi memiliki gaya kognitif FD.…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini sesuai dengan hasil penelitian (Purwati et al, 2022), (Widura et al, 2016), (Ruskandi & Ferdian, 2016), dan (Listiagfiroh & Ellianawati, 2019) yang menyatakan bahwa model guided discovery learning sangat baik digunakan dalam proses pengajaran siswa dengan berbantuan media game dapat meningkatkan kemampuan berpikir kritis siswa sekolah dasar karena siswa antusias dalam proses pembelajaran dan merasa senang jika menggunakan model pembelajaran dan juga media pembelajaran yang variatif.…”
Section: Hasil Dan Pembahasanunclassified